An Overview of Effective Communication in Patient Care Services at Madina Hospital Bukittinggi 2025 - Sonia Pratiwi; Silvia Adi Putri; Iffa Setiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2025)
Effective communication at the patient registration unit of Madina Hospital, Bukittinggi, has not been fully implemented. Registration officers often fail to convey important information, such as changes in doctors’ schedules, resulting in patients waiting for long periods without receiving services. This study aimed to describe effective communication in patient service delivery at Madina Hospital, Bukittinggi, in 2025. A descriptive quantitative approach was employed, involving 40 patients as respondents. Data were collected using a structured questionnaire. The results showed that 22 respondents (55.0%) had a high level of understanding, while 18 respondents (45.0%) had a low level. Regarding patient satisfaction, 25 respondents (62.5%) reported good satisfaction and 15 respondents (37.5%) reported low satisfaction. Positive attitudes were found in 27 respondents (67.5%), while 13 respondents (32.5%) showed negative attitudes. Good interpersonal relationships were reported by 23 respondents (57.5%), and 30 respondents (75.0%) demonstrated positive actions. In conclusion, communication practices at the registration unit require continuous evaluation and improvement to enhance the quality of patient services.